مساهمة في دراسة واقع المركبات الهيدروكربونية الأليفاتية في رسوبيات شاطئ مدينة اللاذقية - محمد, عصام; حويجة, عماد; أغيورلي, أحمد أمير (Latakia University Journal -Basic Sciences Series, 2018)
This study deals with the distribution of aliphatic hydrocarbons (AHs) in tidal sediments of Lattakia coast. The concentrations of aliphatic hydrocarbons were determined in (110) surface samples of sediments taken from seven tidal sites along Lattakia coast, during the period 7 / 5 / 2000 – 21 / 6 / 2001. the technique of Gas Chromatography (GC) which was equipped with a Split/Splitless injection system, Capillary column, Flame Ionization Detector (FID) was used depending on External &Internal Standard solutions. The concentration of total aliphatic hydrocarbons (ΣAHs) in sediment samples ranged between (12.5) ng/g dry wt in AL-seuar park, and (823.8) ng/g dry wt in the blue Coast. The highest concentration was reported in St(c); the reason for the increase may be due to biogenic sources (biodegradation) in this region in general. This study indicates that the concentrations of Aliphatic hydrocarbons in all stations are within world limit (250)ppm, and it is lower than the concentrations reported, in marine sediment–samples from different international regions. <!--[if gte mso 9]> 800x600 <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> تناولت هذه الدراسة توزع الفحوم الهيدروجينية اﻷليفاتية (AHs) في الرسوبيات الشاطئية لمدينة اللاذقية حيث تم تحديد تراكيزها في 110 عينة من العينات الرسوبية الشاطئية السطحية، تم اعتيانها من سبعة مواقع منتشرة على طول شاطئ مدينة اللاذقية وذلك خلال الفترة الممتدة ما بين 7 / 5 / 2000 و21 / 6 / 2001، مستخدمين تقانة الكروماتوغرافيا الغازية (GC) المجهزة بنظام حقن بالتجزئة ودون التجزئة (Split/splitless)، وعمود شعري، وكاشف تشرد اللهب FID ومعتمدين في ذلك على محاليل عيارية خارجية وداخلية. تراوحت تراكيز الفحوم الهيدروجينية اﻷليفاتية الكلية في العينات الرسوبية ما بين (dry wt.) ng/g (12.5) في منتجع الشاطئ الأزرق St(g)، و(dry wt.) ng/g(823.8) في منتزه السوار St(c)، ومن المتوقع أن يعود سبب ارتفاع التراكيز في عينات المحطة St(c) بشكل عام إلى منشأ حيوي (تحلل حيوي). تشير هذه الدراسة إلى أن تراكيز المركبات الأليفاتية هي ضمن الحدود المسموح بها عالمياً ما دون ppm (250)، وهي أخفض من التراكيز المسجلة في عينات رسوبية بحرية من مناطق عالمية مختلفة (جدول 10).